A dope-colored polylactic acid composition, and a preparation method and application thereof

CN122898113APending Publication Date: 2026-10-13SHAOXING MAIBAO TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611324445.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

虽然原液着色的聚乳酸具有色牢度高,外观效果好的优点,但现有原液着色技术仍存在着色剂分散性差、着色均匀性难以保证等问题

Benefits of technology

1.本发明将活性染料负载于经赖氨酸-氨基己酸共聚物修饰的双醛化纤维素纳米晶表面,制成着色剂,再将其与聚乙二醇单甲醚改性聚乳酸共聚物共同引入聚乳酸基体中熔融混合,制成的原液着色聚乳酸组合物力学性能好,抗菌性能佳,采用原液着色聚乳酸组合物制备的聚乳酸纤维着色均匀性和耐热迁移性均得到改善。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898113A_ABST
    Figure CN122898113A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of polylactic acid material, and discloses a stock solution colored polylactic acid composition, a preparation method and application thereof.The present application loads active dye on the surface of dialdehyde modified cellulose nanocrystal modified by lysine-amino hexanoic acid copolymer to make a colorant, utilizes the strong interaction between the polar group and the active dye molecule to anchor the active dye on the surface of the colorant, thereby effectively improving the dispersibility and migration resistance of the dye in the polylactic acid matrix; then the colorant and polyethylene glycol monomethyl ether modified polylactic acid copolymer are jointly introduced into the polylactic acid matrix for melt mixing to prepare the stock solution colored polylactic acid composition, which has good mechanical properties and good antibacterial performance. When the stock solution colored polylactic acid composition is applied to prepare fibers, the polylactic acid fiber coloring uniformity and heat migration resistance are both improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polylactic acid materials technology, specifically to a solution-colored polylactic acid composition, its preparation method, and its application. Background Technology

[0002] Polylactic acid (PLA) is a bio-based biodegradable polyester material made from renewable plant resources, exhibiting excellent biocompatibility and biodegradability. However, PLA suffers from poor toughness and brittleness in practical applications; simultaneously, PLA fibers have poor dyeing properties. Therefore, improving both the mechanical and dyeing properties of PLA is one of the problems that needs to be solved.

[0003] Solution-dyed polylactic acid (PLA) is produced by adding pigments during polymerization, before spinning, and after polymerization. The pigments and polymers are fed into the spinning machine together, and during spinning, the pigment particles are dispersed in the polymer melt. After extrusion through the spinneret, the pigment particles disperse within the fiber. The pigment particles within the fiber absorb, reflect, and refract light, achieving the fiber coloring effect. Although solution-dyed PLA has advantages such as high color fastness and good appearance, existing solution-dyed technologies still suffer from problems such as poor colorant dispersibility and difficulty in ensuring color uniformity. Furthermore, existing PLA materials have low antibacterial properties, making it difficult to meet the increasing demands for antibacterial performance in medical, hygiene, and clothing fields. Therefore, developing a solution-dyed PLA composition that combines excellent coloring performance, good mechanical properties, and antibacterial function is of great significance. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a solution-colored polylactic acid composition, its preparation method, and its application.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a solution-colored polylactic acid composition includes the following steps: Step (1): The lysine-aminohexanoic acid copolymer and the dialdehyde cellulose nanocrystals are mixed and reacted in water, and then post-treated to obtain cellulose nanocrystals loaded with lysine-aminohexanoic acid copolymer. Step (2): Mix cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer and water, disperse by ultrasonication, add reactive dye and sodium chloride for dyeing, and perform post-treatment to obtain colorant; Step (3): Melt-mix polylactic acid, polyethylene glycol monomethyl ether modified polylactic acid copolymer and colorant to obtain original solution colored polylactic acid composition.

[0006] In the above steps, during the preparation of the colorant, the aldehyde groups on the surface of the dialdehyde cellulose nanocrystals undergo a Schiff base reaction with the amino groups in the lysine-aminohexanoic acid copolymer, forming stable chemical bonds. Simultaneously, the polar groups such as the amino groups in the lysine-aminohexanoic acid copolymer can form strong ionic bonds with the reactive dye molecules, anchoring the reactive dye to the surface of the cellulose nanocrystals loaded with the lysine-aminohexanoic acid copolymer. This effectively improves the dispersibility and migration resistance of the dye in the polylactic acid matrix, ensuring uniform dispersion and preventing precipitation. Furthermore, the cellulose nanocrystals in the colorant possess excellent thermal stability, further inhibiting thermal migration of the dye during high-temperature processing and use, thus endowing the polylactic acid composition with excellent color uniformity and thermal migration resistance. In addition, the lysine-aminohexanoic acid copolymer and the Schiff base bonds achieve a synergistic antibacterial effect, giving the polylactic acid composition a long-lasting and stable antibacterial function.

[0007] In the above steps, the colorant and the polyethylene glycol monomethyl ether modified polylactic acid copolymer have a synergistic effect on strengthening and toughening the polylactic acid composition.

[0008] Preferably, in step (1), the mass ratio of lysine-aminocaproic acid copolymer, water, and dialdehyde cellulose nanocrystals is 2-4:80-100:1; the reaction conditions are: reacting for 60-90 minutes at a pH of 7.5-8.5 and a temperature of 50-70℃.

[0009] Preferably, in step (1), the specific post-processing includes the following steps: after the reaction is completed, filter, take the precipitate, wash with water, and freeze dry.

[0010] Preferably, in step (1), the preparation of the lysine-aminohexanoic acid copolymer includes the following steps: L-lysine, 6-aminocaproic acid, and water were mixed and dissolved, reacted, and then post-treated.

[0011] Preferably, in the preparation of the lysine-aminohexanoic acid copolymer, the mass ratio of L-lysine, 6-aminohexanoic acid, and water is 1-2:0.1-0.2:4-6; the reaction conditions are: reaction at 160-180°C for 6-8 hours in a nitrogen atmosphere.

[0012] Preferably, the post-treatment process for preparing the lysine-aminocaproic acid copolymer includes the following steps: after the reaction is completed, cool to room temperature, add 10 mL of ethanol to dissolve, then add 100 mL of ethyl acetate to precipitate, filter to collect the precipitate, add 10 mL of water to dissolve and concentrate by rotary evaporation, and finally freeze-dry.

[0013] Preferably, in step (2), the mass ratio of cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer, water, reactive dye, and sodium chloride is 1:30-50:0.5-0.8:2-4.

[0014] Preferably, in step (2), the specific dyeing process conditions include: heating to 50-60℃ at a heating rate of 1.5-2℃ / min, adjusting the pH value to 8.5-9.5, continuing to heat to 80-90℃, keeping warm for 90-120min under stirring conditions, and then cooling to room temperature at a cooling rate of 1.5-2℃ / min.

[0015] Preferably, in step (2), the reactive dye includes any one of reactive dye red 195, reactive dye yellow 145, and reactive dye blue 194.

[0016] Preferably, in step (2), the post-processing operations include: centrifugation, filtration, washing with water, and freeze drying.

[0017] Preferably, in step (3), the mass ratio of polylactic acid, modified polylactic acid copolymer, and colorant is 90-95:5-10:3-8; the melt mixing conditions are: melt mixing at 185-195℃ for 5-10 minutes.

[0018] Preferably, in step (3), the preparation of polyethylene glycol monomethyl ether modified polylactic acid copolymer includes the following steps: mixing lactide, polyethylene glycol monomethyl ether and p-hydroxycinnamic acid, adding stannous octoate, reacting, purifying and drying after the reaction is completed.

[0019] Preferably, in the preparation of the polyethylene glycol monomethyl ether modified polylactic acid copolymer, the mass ratio of lactide, polyethylene glycol monomethyl ether, p-hydroxycinnamic acid, and stannous octoate is 10:0.5-1.5:2-2.5:0.05-0.06; the reaction conditions are as follows: after heating to 50-70℃, the temperature is increased to 125-135℃ at a heating rate of 1.5-2℃ / min, then increased to 160-180℃ at a heating rate of 1.5-2℃ / min and a vacuum is drawn, and finally the reaction is carried out for 6-10 hours under the conditions of a vacuum degree of 0.095-0.098MPa and a temperature of 160-180℃.

[0020] Preferably, a solution-colored polylactic acid composition is prepared using the method described above for preparing a solution-colored polylactic acid composition.

[0021] Preferably, the application of a solution-dyed polylactic acid composition as described above on polylactic acid fibers.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. In this invention, reactive dyes are loaded onto the surface of bis-aldehyde cellulose nanocrystals modified with lysine-aminohexanoic acid copolymer to form a colorant. This colorant is then introduced into a polylactic acid matrix and melt-mixed with polyethylene glycol monomethyl ether modified polylactic acid copolymer. The resulting solution-colored polylactic acid composition has good mechanical properties and excellent antibacterial properties. The color uniformity and heat migration resistance of polylactic acid fibers prepared using the solution-colored polylactic acid composition are improved.

[0023] In the preparation of the colorant, the aldehyde groups on the surface of the bis-aldehyde cellulose nanocrystals undergo a Schiff base reaction with the amino groups in the lysine-aminohexanoic acid copolymer, forming stable chemical bonds. Simultaneously, the polar groups such as the amino groups in the lysine-aminohexanoic acid copolymer can form strong ionic bonds with the reactive dye molecules, anchoring the reactive dye to the surface of the cellulose nanocrystals loaded with the lysine-aminohexanoic acid copolymer. This effectively improves the dispersibility and migration resistance of the dye in the polylactic acid matrix, ensuring uniform dispersion and preventing precipitation. Furthermore, the cellulose nanocrystals in the colorant possess excellent thermal stability, further inhibiting thermal migration of the dye during high-temperature processing and use, thus endowing the polylactic acid composition with excellent color uniformity and resistance to thermal migration.

[0024] 2. In this invention, dialdehyde cellulose nanocrystals are uniformly dispersed in the polylactic acid (PLA) matrix as a nano-reinforcing filler. Their high specific surface area and rigid structure can effectively transfer and disperse stress, thus providing mechanical reinforcement. On the other hand, the polyethylene glycol monomethyl ether-modified PLA copolymer introduced in this invention serves as a toughening component. Its flexible polyethylene glycol segments can effectively improve the brittleness of PLA, achieving toughening of PLA. The synergistic effect of reinforcement and toughening enables the PLA composition prepared in this invention to maintain high tensile strength while improving elongation at break.

[0025] 3. In this invention, the lysine-aminohexanoic acid copolymer, as an antimicrobial peptide, exhibits excellent antimicrobial activity. Simultaneously, the Schiff base bonds generated by the reaction of the lysine-aminohexanoic acid copolymer with dialdehyde cellulose nanocrystals also possess antimicrobial activity, thereby achieving a synergistic antimicrobial effect and endowing the polylactic acid composition with a long-lasting and stable antimicrobial function. Attached Figure Description

[0026] Figure 1 These are bar graphs of tensile strength and line graphs of elongation at break of the solution-colored polylactic acid compositions prepared in Examples 1-5 and Comparative Examples 1-2 of this invention during mechanical property testing. Figure 2 This is a bar chart showing the average color difference of polylactic acid fiber samples prepared based on the solution-dyed polylactic acid compositions of Examples 1-7 and Comparative Examples 1-2 in the dyeing performance test of this invention. Detailed Implementation

[0027] The present invention will be further illustrated below through specific embodiments. The following embodiments are specific implementations of the present invention, but the implementation of the present invention is not limited to the following embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and are included within the protection scope of the present invention.

[0028] Example 1 This embodiment discloses a method for preparing a solution-colored polylactic acid composition, including the following steps: Step (1): Mix and dissolve 1.3g of L-lysine, 0.13g of 6-aminohexanoic acid and 5g of water, purge with nitrogen, and react at 180℃ for 6h. After the reaction is complete, cool to room temperature, add 10mL of ethanol to dissolve, then add 100mL of ethyl acetate to precipitate, filter to collect the precipitate, add 10mL of water to dissolve, then concentrate by rotary evaporation, and finally freeze dry to obtain lysine-aminohexanoic acid copolymer; The lysine-aminocaproic acid copolymer was dissolved in water, sodium hydroxide was added to adjust the pH to 8, and dialdehyde cellulose nanocrystals were added. The mixture was reacted at 60°C for 60 min. After the reaction was completed, the mixture was filtered, the precipitate was collected, washed with water, and freeze-dried to obtain cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer. The mass ratio of lysine-aminohexanoic acid copolymer, water, and dialdehyde cellulose nanocrystals is 2:80:1. Step (2): Mix 1g of cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer with 50mL of water, ultrasonically disperse for 10min, add 0.8g of reactive dye red 195 and 3g of sodium chloride, heat to 60℃ at a heating rate of 2℃ / min, add potassium carbonate to adjust the pH to 9, continue heating to 80℃, keep warm for 90min under stirring, then cool to room temperature at a cooling rate of 2℃ / min, centrifuge, filter, wash with water, freeze dry to obtain colorant; Step (3): Polylactic acid, polyethylene glycol monomethyl ether modified polylactic acid copolymer and colorant are melt-mixed at 190°C for 5 min in a mass ratio of 95:5:3, and discharged to obtain the original solution colored polylactic acid composition. The polyethylene glycol monomethyl ether modified polylactic acid copolymer is prepared by the following steps: 10g of lactide, 1g of polyethylene glycol monomethyl ether, and 2.3g of p-hydroxycinnamic acid are mixed, and 0.06g of stannous octoate is added. The mixture is heated to 60℃, then heated to 130℃ at a rate of 2℃ / min, and then heated to 160℃ at a rate of 2℃ / min while evacuating. Finally, the mixture is reacted for 8 hours under a vacuum of 0.096MPa and a temperature of 160℃. After the reaction is completed, a crude product is obtained. The crude product is dissolved in acetone, precipitated with ethanol, and the precipitate is dried at 50℃ for 12 hours to obtain the polyethylene glycol monomethyl ether modified polylactic acid copolymer.

[0029] Example 2 This embodiment discloses a method for preparing a solution-colored polylactic acid composition, including the following steps: Step (1): Mix and dissolve 1.3g of L-lysine, 0.13g of 6-aminohexanoic acid and 5g of water, purge with nitrogen, and react at 180℃ for 6h. After the reaction is complete, cool to room temperature, add 10mL of ethanol to dissolve, then add 100mL of ethyl acetate to precipitate, filter to collect the precipitate, add 10mL of water to dissolve, then concentrate by rotary evaporation, and finally freeze dry to obtain lysine-aminohexanoic acid copolymer; The lysine-aminocaproic acid copolymer was dissolved in water, sodium hydroxide was added to adjust the pH to 8, and dialdehyde cellulose nanocrystals were added. The mixture was reacted at 60°C for 60 min. After the reaction was completed, the mixture was filtered, the precipitate was collected, washed with water, and freeze-dried to obtain cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer. The mass ratio of lysine-aminohexanoic acid copolymer, water, and dialdehyde cellulose nanocrystals is 2.5:85:1. Step (2): Mix 1g of cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer with 50mL of water, ultrasonically disperse for 10min, add 0.8g of reactive dye red 195 and 3g of sodium chloride, heat to 60℃ at a heating rate of 2℃ / min, add potassium carbonate to adjust the pH to 9, continue heating to 80℃, keep warm for 95min under stirring, then cool to room temperature at a cooling rate of 2℃ / min, centrifuge, filter, wash with water, freeze dry to obtain colorant; Step (3): Polylactic acid, polyethylene glycol monomethyl ether modified polylactic acid copolymer and colorant are melt-mixed at 190°C for 5 min in a mass ratio of 94:6:4, and discharged to obtain the original solution colored polylactic acid composition. The polyethylene glycol monomethyl ether modified polylactic acid copolymer is prepared by the following steps: 10g of lactide, 1g of polyethylene glycol monomethyl ether, and 2.3g of p-hydroxycinnamic acid are mixed, and 0.06g of stannous octoate is added. The mixture is heated to 60℃, then heated to 130℃ at a rate of 2℃ / min, and then heated to 160℃ at a rate of 2℃ / min while evacuating. Finally, the mixture is reacted for 8 hours under a vacuum of 0.096MPa and a temperature of 160℃. After the reaction is completed, a crude product is obtained. The crude product is dissolved in acetone, precipitated with ethanol, and the precipitate is dried at 50℃ for 12 hours to obtain the polyethylene glycol monomethyl ether modified polylactic acid copolymer.

[0030] Example 3 This embodiment discloses a method for preparing a solution-colored polylactic acid composition, including the following steps: Step (1): Mix and dissolve 1.3g of L-lysine, 0.13g of 6-aminohexanoic acid and 5g of water, purge with nitrogen, and react at 180℃ for 6h. After the reaction is complete, cool to room temperature, add 10mL of ethanol to dissolve, then add 100mL of ethyl acetate to precipitate, filter to collect the precipitate, add 10mL of water to dissolve, then concentrate by rotary evaporation, and finally freeze dry to obtain lysine-aminohexanoic acid copolymer; The lysine-aminocaproic acid copolymer was dissolved in water, sodium hydroxide was added to adjust the pH to 8, and dialdehyde cellulose nanocrystals were added. The mixture was reacted at 60°C for 60 min. After the reaction was completed, the mixture was filtered, the precipitate was collected, washed with water, and freeze-dried to obtain cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer. The mass ratio of lysine-aminohexanoic acid copolymer, water, and dialdehyde cellulose nanocrystals is 3:90:1. Step (2): Mix 1g of cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer with 50mL of water, ultrasonically disperse for 10min, add 0.8g of reactive dye red 195 and 3g of sodium chloride, heat to 60℃ at a heating rate of 2℃ / min, add potassium carbonate to adjust the pH to 9, continue heating to 80℃, keep warm for 105min under stirring, then cool to room temperature at a cooling rate of 2℃ / min, centrifuge, filter, wash with water, freeze dry to obtain colorant; Step (3): Polylactic acid, polyethylene glycol monomethyl ether modified polylactic acid copolymer and colorant are melt-mixed at 190°C for 5 minutes at a mass ratio of 92:8:5.5, and discharged to obtain the original solution colored polylactic acid composition. The polyethylene glycol monomethyl ether modified polylactic acid copolymer is prepared by the following steps: 10g of lactide, 1g of polyethylene glycol monomethyl ether, and 2.3g of p-hydroxycinnamic acid are mixed, and 0.06g of stannous octoate is added. The mixture is heated to 60℃, then heated to 130℃ at a rate of 2℃ / min, and then heated to 160℃ at a rate of 2℃ / min while evacuating. Finally, the mixture is reacted for 8 hours under a vacuum of 0.096MPa and a temperature of 160℃. After the reaction is completed, a crude product is obtained. The crude product is dissolved in acetone, precipitated with ethanol, and the precipitate is dried at 50℃ for 12 hours to obtain the polyethylene glycol monomethyl ether modified polylactic acid copolymer.

[0031] Example 4 This embodiment discloses a method for preparing a solution-colored polylactic acid composition, including the following steps: Step (1): Mix and dissolve 1.3g of L-lysine, 0.13g of 6-aminohexanoic acid and 5g of water, purge with nitrogen, and react at 180℃ for 6h. After the reaction is complete, cool to room temperature, add 10mL of ethanol to dissolve, then add 100mL of ethyl acetate to precipitate, filter to collect the precipitate, add 10mL of water to dissolve, then concentrate by rotary evaporation, and finally freeze dry to obtain lysine-aminohexanoic acid copolymer; The lysine-aminocaproic acid copolymer was dissolved in water, sodium hydroxide was added to adjust the pH to 8, and dialdehyde cellulose nanocrystals were added. The mixture was reacted at 60°C for 60 min. After the reaction was completed, the mixture was filtered, the precipitate was collected, washed with water, and freeze-dried to obtain cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer. The mass ratio of lysine-aminohexanoic acid copolymer, water, and dialdehyde cellulose nanocrystals is 3.5:95:1. Step (2): Mix 1g of cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer with 50mL of water, ultrasonically disperse for 10min, add 0.8g of reactive dye Red 195 and 3g of sodium chloride, heat to 60℃ at a heating rate of 2℃ / min, add potassium carbonate to adjust the pH to 9, continue heating to 80℃, keep warm for 110min under stirring, then cool to room temperature at a cooling rate of 2℃ / min, centrifuge, filter, wash with water, freeze dry to obtain colorant; Step (3): Polylactic acid, polyethylene glycol monomethyl ether modified polylactic acid copolymer and colorant are melt-mixed at 190°C for 5 minutes at a mass ratio of 91:9:7, and discharged to obtain the original solution colored polylactic acid composition. The polyethylene glycol monomethyl ether modified polylactic acid copolymer is prepared by the following steps: 10g of lactide, 1g of polyethylene glycol monomethyl ether, and 2.3g of p-hydroxycinnamic acid are mixed, and 0.06g of stannous octoate is added. The mixture is heated to 60℃, then heated to 130℃ at a rate of 2℃ / min, and then heated to 160℃ at a rate of 2℃ / min while evacuating. Finally, the mixture is reacted for 8 hours under a vacuum of 0.096MPa and a temperature of 160℃. After the reaction is completed, a crude product is obtained. The crude product is dissolved in acetone, precipitated with ethanol, and the precipitate is dried at 50℃ for 12 hours to obtain the polyethylene glycol monomethyl ether modified polylactic acid copolymer.

[0032] Example 5 This embodiment discloses a method for preparing a solution-colored polylactic acid composition, including the following steps: Step (1): Mix and dissolve 1.3g of L-lysine, 0.13g of 6-aminohexanoic acid and 5g of water, purge with nitrogen, and react at 180℃ for 6h. After the reaction is complete, cool to room temperature, add 10mL of ethanol to dissolve, then add 100mL of ethyl acetate to precipitate, filter to collect the precipitate, add 10mL of water to dissolve, then concentrate by rotary evaporation, and finally freeze dry to obtain lysine-aminohexanoic acid copolymer; The lysine-aminocaproic acid copolymer was dissolved in water, sodium hydroxide was added to adjust the pH to 8, and dialdehyde cellulose nanocrystals were added. The mixture was reacted at 60°C for 60 min. After the reaction was completed, the mixture was filtered, the precipitate was collected, washed with water, and freeze-dried to obtain cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer. The mass ratio of lysine-aminohexanoic acid copolymer, water, and dialdehyde cellulose nanocrystals is 4:100:1. Step (2): Mix 1g of cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer with 50mL of water, ultrasonically disperse for 10min, add 0.8g of reactive dye red 195 and 3g of sodium chloride, heat to 60℃ at a heating rate of 2℃ / min, add potassium carbonate to adjust the pH to 9, continue heating to 80℃, keep warm for 120min under stirring, then cool to room temperature at a cooling rate of 2℃ / min, centrifuge, filter, wash with water, freeze dry to obtain colorant; Step (3): Polylactic acid, polyethylene glycol monomethyl ether modified polylactic acid copolymer and colorant are melt-mixed at 190°C for 5 minutes at a mass ratio of 90:10:8, and discharged to obtain the original solution colored polylactic acid composition. The polyethylene glycol monomethyl ether modified polylactic acid copolymer is prepared by the following steps: 10g of lactide, 1g of polyethylene glycol monomethyl ether, and 2.3g of p-hydroxycinnamic acid are mixed, and 0.06g of stannous octoate is added. The mixture is heated to 60℃, then heated to 130℃ at a rate of 2℃ / min, and then heated to 160℃ at a rate of 2℃ / min while evacuating. Finally, the mixture is reacted for 8 hours under a vacuum of 0.096MPa and a temperature of 160℃. After the reaction is completed, a crude product is obtained. The crude product is dissolved in acetone, precipitated with ethanol, and the precipitate is dried at 50℃ for 12 hours to obtain the polyethylene glycol monomethyl ether modified polylactic acid copolymer.

[0033] Example 6 This embodiment discloses a method for preparing a solution-colored polylactic acid composition, including the following steps: Step (1): Mix and dissolve 1.3g of L-lysine, 0.13g of 6-aminohexanoic acid and 5g of water, purge with nitrogen, and react at 180℃ for 6h. After the reaction is complete, cool to room temperature, add 10mL of ethanol to dissolve, then add 100mL of ethyl acetate to precipitate, filter to collect the precipitate, add 10mL of water to dissolve, then concentrate by rotary evaporation, and finally freeze dry to obtain lysine-aminohexanoic acid copolymer; The lysine-aminocaproic acid copolymer was dissolved in water, sodium hydroxide was added to adjust the pH to 8, and dialdehyde cellulose nanocrystals were added. The mixture was reacted at 60°C for 60 min. After the reaction was completed, the mixture was filtered, the precipitate was collected, washed with water, and freeze-dried to obtain cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer. The mass ratio of lysine-aminohexanoic acid copolymer, water, and dialdehyde cellulose nanocrystals is 2:80:1. Step (2): Mix 1g of cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer with 50mL of water, sonicate for 10min, add 0.8g of reactive dye yellow 145 and 3g of sodium chloride, heat to 60℃ at a heating rate of 2℃ / min, add potassium carbonate to adjust the pH to 9, continue heating to 80℃, keep warm for 90min under stirring, then cool to room temperature at a cooling rate of 2℃ / min, centrifuge, filter, wash with water, freeze dry to obtain colorant; Step (3): Polylactic acid, polyethylene glycol monomethyl ether modified polylactic acid copolymer and colorant are melt-mixed at 195°C for 5 minutes at a mass ratio of 95:5:3, and discharged to obtain the original solution colored polylactic acid composition. The polyethylene glycol monomethyl ether modified polylactic acid copolymer is prepared by the following steps: 10g of lactide, 1g of polyethylene glycol monomethyl ether, and 2.3g of p-hydroxycinnamic acid are mixed, and 0.06g of stannous octoate is added. The mixture is heated to 60℃, then heated to 130℃ at a rate of 2℃ / min, and then heated to 160℃ at a rate of 2℃ / min while evacuating. Finally, the mixture is reacted for 8 hours under a vacuum of 0.096MPa and a temperature of 160℃. After the reaction is completed, a crude product is obtained. The crude product is dissolved in acetone, precipitated with ethanol, and the precipitate is dried at 50℃ for 12 hours to obtain the polyethylene glycol monomethyl ether modified polylactic acid copolymer.

[0034] Example 7 This embodiment discloses a method for preparing a solution-colored polylactic acid composition, including the following steps: Step (1): Mix and dissolve 1.3g of L-lysine, 0.13g of 6-aminohexanoic acid and 5g of water, purge with nitrogen, and react at 180℃ for 6h. After the reaction is complete, cool to room temperature, add 10mL of ethanol to dissolve, then add 100mL of ethyl acetate to precipitate, filter to collect the precipitate, add 10mL of water to dissolve, then concentrate by rotary evaporation, and finally freeze dry to obtain lysine-aminohexanoic acid copolymer; The lysine-aminocaproic acid copolymer was dissolved in water, sodium hydroxide was added to adjust the pH to 8, and dialdehyde cellulose nanocrystals were added. The mixture was reacted at 60°C for 60 min. After the reaction was completed, the mixture was filtered, the precipitate was collected, washed with water, and freeze-dried to obtain cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer. The mass ratio of lysine-aminohexanoic acid copolymer, water, and dialdehyde cellulose nanocrystals is 2:80:1. Step (2): Mix 1g of cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer with 50mL of water, ultrasonically disperse for 10min, add 0.8g of reactive dye blue 194 and 3g of sodium chloride, heat to 60℃ at a heating rate of 2℃ / min, add potassium carbonate to adjust the pH to 9, continue heating to 80℃, keep warm for 90min under stirring, then cool to room temperature at a cooling rate of 2℃ / min, centrifuge, filter, wash with water, freeze dry to obtain colorant; Step (3): Polylactic acid, polyethylene glycol monomethyl ether modified polylactic acid copolymer and colorant are melt-mixed at 185°C for 5 minutes at a mass ratio of 95:5:3, and discharged to obtain the original solution colored polylactic acid composition. The polyethylene glycol monomethyl ether modified polylactic acid copolymer is prepared by the following steps: 10g of lactide, 1g of polyethylene glycol monomethyl ether, and 2.3g of p-hydroxycinnamic acid are mixed, and 0.06g of stannous octoate is added. The mixture is heated to 60℃, then heated to 130℃ at a rate of 2℃ / min, and then heated to 160℃ at a rate of 2℃ / min while evacuating. Finally, the mixture is reacted for 8 hours under a vacuum of 0.096MPa and a temperature of 160℃. After the reaction is completed, a crude product is obtained. The crude product is dissolved in acetone, precipitated with ethanol, and the precipitate is dried at 50℃ for 12 hours to obtain the polyethylene glycol monomethyl ether modified polylactic acid copolymer.

[0035] Comparative Example 1 This comparative example discloses a method for preparing a solution-colored polylactic acid composition, comprising the following steps: Polylactic acid, polyethylene glycol monomethyl ether modified polylactic acid copolymer, reactive dye Red 195, and cellulose nanocrystals were melt-mixed at 190°C for 5 minutes in a mass ratio of 95:5:0.5:2, and the mixture was discharged to obtain a solution-colored polylactic acid composition. The polyethylene glycol monomethyl ether modified polylactic acid copolymer is prepared by the following steps: 10g of lactide, 1g of polyethylene glycol monomethyl ether, and 2.3g of p-hydroxycinnamic acid are mixed, and 0.06g of stannous octoate is added. The mixture is heated to 60℃, then heated to 130℃ at a rate of 2℃ / min, and then heated to 160℃ at a rate of 2℃ / min while evacuating. Finally, the mixture is reacted for 8 hours under a vacuum of 0.096MPa and a temperature of 160℃. After the reaction is completed, a crude product is obtained. The crude product is dissolved in acetone, precipitated with ethanol, and the precipitate is dried at 50℃ for 12 hours to obtain the polyethylene glycol monomethyl ether modified polylactic acid copolymer.

[0036] Comparative Example 2 This comparative example discloses a method for preparing a solution-colored polylactic acid composition, comprising the following steps: Step (1): Mix and dissolve 1.3g of L-lysine, 0.13g of 6-aminohexanoic acid and 5g of water, purge with nitrogen, and react at 180℃ for 6h. After the reaction is complete, cool to room temperature, add 10mL of ethanol to dissolve, then add 100mL of ethyl acetate to precipitate, filter to collect the precipitate, add 10mL of water to dissolve, then concentrate by rotary evaporation, and finally freeze dry to obtain lysine-aminohexanoic acid copolymer; The lysine-aminocaproic acid copolymer was dissolved in water, sodium hydroxide was added to adjust the pH to 8, and dialdehyde cellulose nanocrystals were added. The mixture was reacted at 60°C for 60 min. After the reaction was completed, the mixture was filtered, the precipitate was collected, washed with water, and freeze-dried to obtain cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer. The mass ratio of lysine-aminohexanoic acid copolymer, water, and dialdehyde cellulose nanocrystals is 2:80:1. Step (2): Mix 1g of cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer with 50mL of water, ultrasonically disperse for 10min, add 0.8g of reactive dye red 195 and 3g of sodium chloride, heat to 60℃ at a heating rate of 2℃ / min, add potassium carbonate to adjust the pH to 9, continue heating to 80℃, keep warm for 90min under stirring, then cool to room temperature at a cooling rate of 2℃ / min, centrifuge, filter, wash with water, freeze dry to obtain colorant; Step (3): Polylactic acid and colorant are melt-mixed at 190°C for 5 minutes at a mass ratio of 100:3, and the mixture is discharged to obtain the original solution colored polylactic acid composition.

[0037] In the above examples and comparative examples, the dialdehyde cellulose nanocrystals were commercially available, with a diameter of 10-30 nm, a length of 200-500 nm, and an aldehyde content of 2.6 mmol / g; the cellulose nanocrystals were commercially available, with a diameter of 10-30 nm and a length of 200-500 nm; the polyethylene glycol monomethyl ether was MPEG2000; the reactive dyes Red 195, Yellow 145, and Blue 194 were all commercially available; and the polylactic acid was from Nature Works, model 6201D.

[0038] Test case (1) The comprehensive performance of the solution-colored polylactic acid compositions prepared in Examples 1-5 and Comparative Examples 1-2 was tested. The specific test results are shown in Table 1: Table 1

[0039] The tests for each indicator in Table 1 were conducted according to the following standards: tensile strength and elongation at break were tested according to GB / T 1040-2006 "Determination of Tensile Properties of Plastics"; antibacterial rate was determined according to GB / T31402-2015 "Test Method for Antibacterial Properties of Plastic Surfaces", and Escherichia coli was selected as the strain.

[0040] (2) The solution-dyed polylactic acid compositions prepared in Examples 1-7 and Comparative Examples 1-2 were spun to obtain polylactic acid fibers. The dyeing properties of the polylactic acid fibers were tested, and the specific test results are shown in Table 2.

[0041] The spinning process includes the following steps: the solution-dyed polylactic acid compositions prepared in Examples 1-7 and Comparative Examples 1-2 are spun at a spinning speed of 2000 m / min and a temperature of 235°C, with a draw ratio of 2, to obtain polylactic acid fiber samples 1-9.

[0042] Table 2

[0043] In Table 2, color uniformity is represented by color difference. The test was conducted using a Color icontrol colorimeter. The test method was as follows: Before the test, polylactic acid fiber samples 1-9 were cut into four equal lengths and made into color cards. Then, the color value of each color card was tested using the Color icontrol colorimeter. During the test, three points were taken from both the front and back of each color card. The average value was taken as the color value of the color card. The color difference ΔE between the color cards was calculated using the instrument's built-in software, and the average value was taken.

[0044] Heat migration resistance is represented by heat migration resistance grade. The test method is as follows: place polylactic acid fiber samples 1-9 in water at 100℃ with a bath ratio of 50:1. After 15 minutes, take out samples 1-9 and rate the color of the aqueous solution using a gray scale for assessing staining and a gray scale for assessing discoloration.

[0045] As can be seen from the results in Tables 1 and 2, the solution-dyed polylactic acid composition prepared by the present invention has excellent mechanical properties and antibacterial properties, and the color uniformity and heat migration resistance of the fibers after spinning are also good.

[0046] In Comparative Example 1, the cellulose nanocrystals were not surface-modified. Due to the lack of interaction between the reactive dye and the unmodified cellulose nanocrystals, the dye was difficult to be effectively loaded onto the nanocrystal surface, resulting in uneven dispersion and easy migration and aggregation of the dye in the polylactic acid matrix. At the same time, the unmodified cellulose nanocrystals had poor interfacial compatibility with the polylactic acid matrix and were prone to aggregation, thus affecting the mechanical properties of the polylactic acid composition. In addition, due to the lack of lysine-aminohexanoic acid copolymer as an antibacterial component, the mechanical properties and antibacterial properties of the polylactic acid composition in Comparative Example 1 were lower than those of the Example, and the dyeing performance of Sample 8 prepared based on Comparative Example 1 was also lower than that of the Example.

[0047] In Comparative Example 2, no polyethylene glycol monomethyl ether modified polylactic acid copolymer was added as a toughening component. Due to the lack of the toughening effect of flexible polyethylene glycol segments, the polylactic acid composition could not effectively disperse and absorb impact energy when subjected to stress, resulting in a significant reduction in elongation at break and lower overall toughness compared to the Example.

[0048] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.

Claims

1. A method for preparing a solution-colored polylactic acid composition, characterized in that, Includes the following steps: Lysine-aminohexanoic acid copolymer and dialdehyde cellulose nanocrystals were mixed and reacted in water, followed by post-treatment to obtain cellulose nanocrystals loaded with lysine-aminohexanoic acid copolymer. Cellulose nanocrystals loaded with lysine-aminohexanoic acid copolymer were mixed with water, ultrasonically dispersed, dyed with reactive dye and sodium chloride, and post-treated to obtain a colorant. Polylactic acid, polyethylene glycol monomethyl ether modified polylactic acid copolymer, and colorant are melt-mixed to obtain a solution-colored polylactic acid composition.

2. The method for preparing a solution-colored polylactic acid composition according to claim 1, characterized in that, When preparing the cellulose nanocrystals loaded with the lysine-aminohexanoic acid copolymer, the mass ratio of the lysine-aminohexanoic acid copolymer, water, and dialdehyde cellulose nanocrystals is 2-4:80-100:1; the reaction conditions are: a pH of 7.5-8.5 and a temperature of 50-70℃ for 60-90 min.

3. The method for preparing a solution-colored polylactic acid composition according to claim 1, characterized in that, The preparation of the lysine-aminohexanoic acid copolymer includes the following steps: mixing and dissolving L-lysine, 6-aminohexanoic acid, and water, reacting, and post-treatment; wherein the mass ratio of L-lysine, 6-aminohexanoic acid, and water is 1-2:0.1-0.2:4-6; the reaction conditions are: reacting at 160-180℃ for 6-8 hours in a nitrogen atmosphere.

4. The method for preparing a solution-colored polylactic acid composition according to claim 1, characterized in that, When preparing the colorant: the mass ratio of cellulose nanocrystals loaded with lysine-aminocaproic acid copolymer, water, reactive dye, and sodium chloride is 1:30-50:0.5-0.8:2-4.

5. The method for preparing a solution-colored polylactic acid composition according to claim 1, characterized in that, When preparing the colorant, the specific dyeing process conditions include: heating to 50-60℃ at a heating rate of 1.5-2℃ / min, adjusting the pH value to 8.5-9.5, continuing to heat to 80-90℃, keeping warm for 90-120min under stirring, and then cooling to room temperature at a cooling rate of 1.5-2℃ / min.

6. The method for preparing a solution-colored polylactic acid composition according to claim 1, characterized in that, The mass ratio of polylactic acid, modified polylactic acid copolymer, and colorant is 90-95:5-10:3-8; the melt mixing conditions are: melt mixing at 185-195℃ for 5-10 minutes.

7. The method for preparing a solution-colored polylactic acid composition according to claim 1, characterized in that, The preparation of the polyethylene glycol monomethyl ether modified polylactic acid copolymer includes the following steps: mixing lactide, polyethylene glycol monomethyl ether, and p-hydroxycinnamic acid, adding stannous octoate, reacting, purifying after the reaction, and drying.

8. The method for preparing a solution-colored polylactic acid composition according to claim 7, characterized in that, When preparing the polyethylene glycol monomethyl ether modified polylactic acid copolymer: the mass ratio of lactide, polyethylene glycol monomethyl ether, p-hydroxycinnamic acid, and stannous octoate is 10:0.5-1.5:2-2.5:0.05-0.06; the reaction conditions are as follows: after heating to 50-70℃, the temperature is increased to 125-135℃ at a heating rate of 1.5-2℃ / min, then increased to 160-180℃ at a heating rate of 1.5-2℃ / min and a vacuum is drawn, and finally the reaction is carried out for 6-10 hours under the conditions of a vacuum degree of 0.095-0.098MPa and a temperature of 160-180℃.

9. A solution-colored polylactic acid composition prepared by the method for preparing the solution-colored polylactic acid composition as described in claims 1-8.

10. The application of the solution-dyed polylactic acid composition as described in claim 9 on polylactic acid fibers.